Determination of Traffic Patterns on Urban Roads - Ladislav Bartuska; Karel Jerabek; Li Chenguang (Communications - Scientific letters of the University of Zilina, 2017)
Traffic volume indicates the use and the capacity of road infrastructure. In traffic engineering the traffic volume is generally stated as so-called Annual Average Daily Traffic (abbreviated as AADT), which can be determined from a short-time traffic survey according to the TP 189 methodology. The issue of AADT determination is in fact simplified on the urban roads where we can find types of traffic patterns different from those dealt with in theTP 189 methology.The introductory part of the paper deals with the theory of determination of traffic volumes and the theory of traffic flow. The aim of the article is to demonstrate traffic patterns on specific urban roads determined by the authors according to the idea that different types of traffic flows on urban roads within the different urban areas may be found. The paper deals with the issue of factors influencing the traffic flows within the city as well.